Inventory of Moss Plant Types in Kedah Rainforest Lodges Blangjerango District, Gayo Lues Regency - Ismawati Ismawati (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research on Inventory of Moss Plant Types in the Kedah Rainforest Lodges Blangjerango District Gayo Lues Regency Penosan Village was conducted in August to September 2019. This study aims to determine the types of moss plants in the Kedah Rainforest Lodges Area Blangjerango District, Gayo Lues District. The approach and the type of research is descriptive. The area of Rainforest Lodges Kedah is 30 ha, the total area used in this study is 3 ha consisting of 3 stations determined based on the direction of the wind, the area of each station is 1 ha. The study was conducted using exploratory methods conducted by roaming. The results obtained 55 species of mosses which belong to 23 families. The species 0f moss plant substrate in the Rainforest Lodges Kedah can be found in moist habitats such as trees, wood, soil, and rocks.